Answer:
The answer is the third option
Part 1) [tex]csc(\theta)=-\frac{\sqrt{373}}{18}[/tex]
Part 2) [tex]sin(\theta)=-\frac{18}{\sqrt{373}}[/tex]
Part 3) [tex]tan(\theta)=-\frac{18}{7}[/tex]
Part 4) [tex]sec(\theta)=\frac{\sqrt{373}}{7}[/tex]
Part 5) [tex]cos(\theta)=\frac{7}{\sqrt{373}}[/tex]
Step-by-step explanation:
we know that
If angle theta lie on Quadrant IV
then
The function sine is negative
The function cosine is positive
The function tangent is negative
The function secant is positive
The function cosecant is negative
step 1
Find [tex]csc(\theta)[/tex]
we know that
[tex]cot^{2} (\theta)+1=csc^{2} (\theta)[/tex]
we have
[tex]cot(\theta)=-\frac{7}{18}[/tex]
substitute
[tex](-\frac{7}{18})^{2}+1=csc^{2} (\theta)[/tex]
[tex]\frac{49}{324}+1=csc^{2} (\theta)[/tex]
[tex]\frac{373}{324}=csc^{2} (\theta)[/tex]
square root both sides
[tex]csc(\theta)=-\frac{\sqrt{373}}{18}[/tex]
step 2
Find [tex]sin(\theta)[/tex]
we know that
[tex]csc(\theta)=\frac{1}{sin(\theta)}[/tex]
we have
[tex]csc(\theta)=-\frac{\sqrt{373}}{18}[/tex]
therefore
[tex]sin(\theta)=-\frac{18}{\sqrt{373}}[/tex]
step 3
Find [tex]tan(\theta)[/tex]
we know that
[tex]tan(\theta)=\frac{1}{cot(\theta)}[/tex]
we have
[tex]cot(\theta)=-\frac{7}{18}[/tex]
therefore
[tex]tan(\theta)=-\frac{18}{7}[/tex]
step 4
Find [tex]sec(\theta)[/tex]
we know that
[tex]tan^{2} (\theta)+1=sec^{2} (\theta)[/tex]
we have
[tex]tan(\theta)=-\frac{18}{7}[/tex]
substitute
[tex](-\frac{18}{7})^{2}+1=sec^{2} (\theta)[/tex]
[tex]\frac{324}{49}+1=sec^{2} (\theta)[/tex]
[tex]\frac{373}{49}=sec^{2} (\theta)[/tex]
square root both sides
[tex]sec(\theta)=\frac{\sqrt{373}}{7}[/tex] -----> is positive
step 5
Find [tex]cos(\theta)[/tex]
we know that
[tex]sec(\theta)=\frac{1}{cos(\theta)}[/tex]
we have
[tex]sec(\theta)=\frac{\sqrt{373}}{7}[/tex]
therefore
[tex]cos(\theta)=\frac{7}{\sqrt{373}}[/tex]